PENGARUH STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Chusnitah, Nur Maghfirotu; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of financial performance which is proxy by the capital structur,corporate growth, firm size, and profitability to the firm value. The population is automotive companies whichare listed in Indonesia Stock Exchange, the sample collection technique using purposive sampling. The numberof samples are 10 companies, with the number of observations 50 in 2012-2016 periods. The analysis model hasbeen performed by using multiple linear regressions analysis.Based on the result of the test, it can be concludedthat: Capital structure give negative influence to the firm value, this result is described by the assumption oftarget point of capital structure is above the optimal point in the addition of debt. Firm growth gives positiveinfluence to the firm value, it describes that good company growth can give positive signal to the firm value.Firm size gives positive influence to the firm value, it indicates the availability of capital adequacy has made thecompany is able to maximize its performance. Therefore, it will generate high profits to the firm value as well.Profitability gives positive influence to the firm value, it shows that when the obtained profit is getting high,which will increase its firm value will be high as well.Keywords: Capital structure, corporate growth, firm size, profitability, firm value.